Heavy metal contents in the muscle tissue of Capoeta trutta fish species in relation to body size and sex - Düşükcan, Mustafa (My University, 2013)
In this study, the levels of zinc (Zn), iron (Fe), copper (Cu), cobalt (Co), cadmium (Cd), chromium (Cr), lead (Pb), arsenic (As), nickel (Ni), and mercury (Hg) levels in the muscle of Capoeta trutta (Heckel, 1843) from Atatürk Dam Lake (Turkey) were investigated. Only Fe, Cu and Zn were detected in the muscle tissues samples. Co, Cd, Cr, Pb, As, Ni and Hg were not found in detectable levels according to results obtained by ICP. The concentration of heavy metals showed differences according to weight, length, sex and age of fish. The results were discussed and compared with tolerable values for heavy metals provided from the Environmental Protection Agency (EPA) and Food and Agriculture Organization (FAO) to determine whether this species has any risk for human consumption.

Bu çalışmada, Atatürk Baraj Gölü’nden elde edilen Capoeta trutta (Heckel, 1843)’un kas dokusundaki çinko (Zn), demir (Fe), bakır (Cu), kobalt (Co), cadmium (Cd), krom (Cr), kurşun (Pb), arsenik (As), nikel (Ni) ve civa (Hg) düzeyleri araştırıldı. Kas dokusunda yalnız Cu, Fe, Zn elementlerinin miktarları belirlendi. Co, Cd, Cr, Pb, As, Ni ve Hg elementlerinin miktarı ICP cihazının okuma duyarlılığının altında olduğundan belirlenemedi. Ağır metal konsantrasyonunun balığın ağırlık, uzunluk, cinsiyet ve yaşına bağlı olarak değişiklik gösterdiği belirlendi. Bu türün insanlar tarafından tüketilmesinin herhangi bir risk taşıyıp taşımadığı EPA ve FAO tarafından önerilen kabul edilebilir değerler ile karşılaştırılarak tartışıldı.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Capoeta trutta; Heavy metals; Atatürk Dam Lake; Turkey; Ağır metal; Atatürk Baraj Gölü; Türkiye